(untitled) (Proceedings of International Educators Conference, 2023)
To create a comprehensive system of organizing spiritual and educational processes in our country, to improve the organizational and scientific aspects of protecting students from spiritual threats, in the dark direction, state organizations: general education schools, neighborhood, which is considered a social institution, and parents great importance is attached to effective establishment of social cooperation.